2012
DOI: 10.1186/1471-2261-12-104
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of admission heart rate in patients with ST-segment elevation myocardial infarction: Role of Type 2 diabetes mellitus

Abstract: BackgroundIt’s unknown whether the prognostic value of admission heart rate (HR) was different in patients with ST-segment elevation myocardial infarction (STEMI) with or without concomitant type 2 diabetes mellitus (T2DM).MethodsConsecutive STEMI patients who presented within 12 hours of symptom onset were recruited from 274 hospitals in China. Participants were stratified into quartiles by admission HR. Baseline characteristics, current therapeutic recommenda- tions, laboratory biochemical tests, 30-day all-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Indeed, in a recent study in early normotensive sepsis, MFI was 3.00 (2.73-3.00) (35). The observed association between macrohemodynamic variables, lactate levels, and mortality confirms the present clinical paradigm (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Notably, a single measurement of blood pressure or HR, irrespective of disease state and timeframe, provided predictive value.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, in a recent study in early normotensive sepsis, MFI was 3.00 (2.73-3.00) (35). The observed association between macrohemodynamic variables, lactate levels, and mortality confirms the present clinical paradigm (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Notably, a single measurement of blood pressure or HR, irrespective of disease state and timeframe, provided predictive value.…”
Section: Discussionsupporting
confidence: 70%
“…[2229] Evidence also showed that admission HR values could independently predict mortality in patients with AMI. [20,30–32] Benjamin et al have demonstrated that increasing HR >65 bpm was associated with worse outcomes, including all-cause and cause-specific mortality, as well as adverse cardiovascular events in patients with AF. [33] HR variability is controlled by a balance between sympathetic and parasympathetic systems, and persistently high resting HRs are seen in stressful situations, chronic illness, and physical inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…19 This effect of the heart rate on outcome is further worsened by diabetes mellitus. 20 Our study showed that the rate of reperfusion failure increased with advancing age. In addition, elderly patients who are admitted with MI have higher rate of stroke, cardiogenic shock, bleeding and reinfarction.…”
mentioning
confidence: 53%